Accumulation of dry matter, absorption and distribution of nutrients by six Brazilian potatoes cultivars (Solanum Tuberosum L.) - Macedo, M. C. Motta; Haag, H. P.; Gallo, J. R. (Anais da Escola Superior de Agricultura Luiz de Queiroz, 1977)
The main object of the present study was to obtain information on the accumulation of dry matter, absorption and distribuition of nutrients by six potatoes cultivars (ARACY, ITAIQUARA, ABAETÊ, IAC-IIII, TEBERÊ, IAO-5603). The experiment was conducted on a Red Dark Latossol at the Experimental Station in Capão Bonito, São Paulo. The experimental design utilized was a randonized complete block with four replications. Rates of nutrient utilized were as follows: 70 Kg/ha of N; Kg/ha of P2O5 and 150 kg/ha of K6O at planting time. All plots received an application of 70 Kg/ha of N in the dressin form, 45 days later. The stands corresponded to a population of 35,000 plants perhectare. Sampling of the plants were executed at intervals of 20 days until maturity. Dry matter contents of leaves, stms and tubers were determined, as well as the concentration of N, P, K, Ca, Mg, S, Cu, Fe.